An integrated perspective of TOE framework and innovation diffusion in broadband mobile applications adoption by enterprises - Chui-Yu Chiu; Shi Chen; Chun-Liang Chen (International Journal of Management, Economics and Social Sciences (IJMESS), 2017)
This study aimed at exploring the critical factors for enterprises to adopt broadband mobile applications. The results are expected to guide enterprises to strengthen their competitiveness. Further, since the broadband mobile applications were integrated with many characteristics of information communication technologies, this study combined the Technology-Organization-Environment (TOE) framework and Diffusion of Innovation Theory in an effort to establish a comprehensive view and to increase the level of understanding. The Structural Equation Modeling and AMOS were applied for analysis; which discovered that the adoption of broadband mobile applications by enterprises is significantly affected by technological, organizational and environmental contexts. This paper also identified eleven critical factors from technological, organizational and environmental aspects, as well as two vital control variables. Based on the research outcome, this paper conducted an in-depth discussion and drew conclusions. Finally, the research implications were provided.
Keywords: L96; O32; 330; Broadband mobile application; technology-organization-environment framework (TOE framework); diffusion of innovation theory; enterprise's adoption; critical factors